Narasi Pemberdayaan UMKM oleh Lembaga Keuangan Syariah sebagai Pertaruhan Pembangunan Ekonomi Islam - Zuchroh, Imama (Prodi Ekonomi Syariah Universitas Majalengka, 2024)
In Islam the term economic development is the process of allaviating poverty and provision of ease, comfort and decency in life (A process that has the effect of reducing the level of poverty and creating peace, comfort and moral system in life). One approach is to reduce poverty with the existence of Islamic Financial Institutions where capital springs for micro, small and medium enterprises are flowed from there. Islamic microfinance institutions in their activities will offer products and services by applying Islamic values, which will provide benefits to the community. This research uses library research with efforts to search for literature references related to those related to the subject matter discussed descriptively. Then of course there is a big gamble if Islamic Financial Institutions do not carry out their main role or only profit-oriented, the Micro, Small, Medium Enterprises (MSMEs) sector, which is very important for the nation's economy, will be hampered and constrained, and Islamic economic development is only on the horizon of hope.